Odpowiedzi

Najlepsza Odpowiedź!
2010-02-15T17:38:31+01:00
6x + 2y + 1 = 2x - 3
2x - 3 = 2y - x +2

6x+ 2y- 2x= -3-1
2x-2y+x= 2+3

4x+2y= - 4
3x - 2y= 5

7x= 1
-2y= 5- 3x

x= jedna siódma
-2y= 5 - trzy siódme

x= jedna siódma
-2y= 32/7(ułamek)

x= jedna siódma
y= - (szesnaście siódmy)
2 1 2
2010-02-15T17:42:05+01:00
6x + 2y + 1 = 2x - 3
2x - 3 = 2y - x +2

4x+2y=-4
3x-2y=5

7x=1 /:7
x=1/7
2y=-4-4x

x=1/7
2y=-4-4*1/7

x=1/7
2y=-4-4/7

x=1/7
2y=-4⁴₇ /:2

x=1/7
y=-4⁴₇:2

x=1/7
y=-32/7*2/1

x=1/7
y=-64/7

x=1/7
y=-9i1/7
PS liczę na naj;)

2 1 2